Paciente de 19 años de sexo masculino con neumonía asociada a la ventilación mecánica. - Ortega Onofre, Julissa Elizabeth (2020)
The present clinical case is about a 19-year-old male patient with a diagnosis of HIV plus pneumonia associated with ventilation that emerged as a complication after the patient's admission to the intensive care unit. Pneumonia associated with mechanical ventilation is the first cause of morbidity and mortality in patients who are under mechanical ventilation through an endotracheal tube or a tracheostomy, this occurs because patients are under sedation, they are not aware of what is impossible to eliminate volunteer of secretions accumulated in the airway. Thanks to this study it is possible to know the risk factors that lead to the appearance of pneumonia associated with ventilation and at the same time know what are the measures that the health professional must take to avoid this critical complication for the critical patient. The objective of this case is to decide the risk factors that lead to the appearance of pneumonia associated with mechanical ventilation. In conclusion, the reduction of this type of pneumonia remains one of the main problems for public health and its prevention of vital importance in those patients who are subjected to mechanical ventilation, although there are several preventive measures in the reduction of bacteria in the pathway The main airway is still aspiration prevention since this is the main route of these microorganisms to reach the patient's airway.